Corporate Criminal Law Liability in Corruption Crimes Based on Perma RI Number 13 of 2016 - Ibnu Aburizal Nashruddien Ms; Sari Mandiana; Jusup Jacobus Setyabudhi (Publikasi Indonesia, 2024)
In Indonesian law, both individuals and legal entities such as corporations are recognized as legal subjects. Corporations, which are governed by civil law, are now increasingly associated with crime, particularly Corporate Crime. Although initially disputed, it is now accepted that legal entities can be involved in criminal acts and that corporations should be held accountable for their unlawful actions. Corporate Crime encompasses situations where corporations break the law for their benefit, often in disregard of applicable regulations and norms. This development marks a shift in criminal law from targeting individuals to also holding corporations accountable. Therefore, principles such as Vicarious Liability and Strict Liability become the basis for establishing legal liability for corporations. These principles ensure that corporations are responsible for their actions, similar to the liability imposed on individuals. Since the legal construction in Perma RI No. 13 Year 2016 is different from individuals, corporations require specific legal principles to regulate their liability. Concepts such as Vicarious Liability, Strict Liability, and others become important pillars in imposing responsibility on corporations. Recognizing corporations as perpetrators of criminal acts shows the evolution of the legal system to adjust to the complexity of modern business practices and uphold justice in an ever-changing society.